Geographic distributions of Pseudopaludicola boliviana and congeneric long-legged species (Anura: Leiuperinae) - Andrade, Felipe Silva de; Haga, Isabelle Aquemi; Lyra, Mariana Lúcio [UNESP]; Gazoni, Thiago [UNESP]; Zaracho, Victor; Haddad, Célio Fernando Baptista [UNESP]; Toledo, Luís Felipe; Giaretta, Ariovaldo Antonio (Taylor & Francis, 2020)
In recent years, the taxonomic knowledge of Pseudopaludicola has increased and it is currently possible to elucidate aspects of the species within this genus such as their geographic distributions. Here we accessed new data on geographic distribution of P. boliviana and three long-legged species of the P. saltica group (P. saltica, P. murundu, and P. jaredi). Based on morphometric, acoustic and genetic data, we accessed the specific status of long-legged specimens from Chapada dos Veadeiros highlands and attributed them to the P. murundu. We also performed a phylogenetic analysis including several populations of the three species. Based on this novel dataset, we discussed the geographical distributions of P. saltica, P. murundu, and P. jaredi, providing new records for them. Pseudopaludicola boliviana is one of the five species of the P. pusilla group and it is thought to be a widely distributed species based on its morphology. Hence, we evaluated the geographic distribution of P. boliviana, using novel acoustic data of specimens from Argentina, Northern Brazil, and Bolivia.
Keywords: cryptic species; frogs; integrative taxonomy; South America; zoogeography